STUDI PENGARUH PENAMBAHAN LIMBAH IKAN PADA PROSES PEMBUATAN PUPUK CAIR DARI URIN SAPI TERHADAP KANDUNGAN UNSUR HARA MAKRO (CNPK) - Fitri Indriani; Endro Sutrisno; Sri Sumiyati (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTCow urine contains a high element of nitrogen that can be utilized as a liquid fertilizer. In the process of making liquid fertilizer, addition of fish waste is expected to increase the nutrients content. This study aims to analyze the content of CNPK liquid fertilizer from cow urine with the addition of fish waste. This goal is traced by varying the amount of fish waste addition (0, 10, 20, 30, 40, and 50) g and day tests CNPK content analysis (before and after fermented). This liquid fertilizer using anaerobic fermentation technology for the past 14 days with the addition of banana roots MOL as bioactivator. The results showed that the addition of cow urine with 20 grams of fish waste is the most effective with C-organic content of 4.41%, Ntotal by 0.62%, amounting to 0.58% P2O5 and K2O by 1.30% however, this liquid fertilizer is not eligible to Permentan No.70/Permentan/SR.140/10/2011 about pupuk organik, pupuk hayati, dan pembenah tanah.